The global state of research in stem cells therapy for spinal cord injury (2003–2022): a visualized analysis - Chen, Taoyu; Zhu, Jiaying; Wang, Gang; Sun, Jinlei; Ma, Xiaofeng; Tian, Lijun; Zhang, Meiling; Wang, Fengyan; Yu, Ze (Frontiers in Neuroscience, 2024)
Objective Our study aimed to visualize the global status and frontiers in stem cell therapy for spinal cord injury by using bibliometric methodology. Methods Publication citation information related to stem cell therapy for spinal cord injury (SCI) studies between 2003 and 2022 was retrieved from the Web of Science Core Collection database. For the visualized study, VOS viewer software and Graph Pad Prism 9.5 were used to perform bibliometric analysis of included data and publication number statistics in stem cell therapy for the SCI domain. Results A total of 6,686 publications were retrieved. The USA and China made the highest contributions to global research with the highest number of citations and link strength. The journal Experimental Neurology ranks as the top journal, combining the publication amount and bibliometrics results. The University of Toronto, based in Canada, was the first-ranking institution. The directions of the current study could be divided into five clusters. The research of Transplantation and Regenerative Medicine and Neurosciences Mechanism Research may be the emerging frontiers in this domain. Conclusion In summary, stem cell therapy for spinal cord injuries is poised for more valuable advances.